Accurate weighing and dilution-assisted plasma microsampling (AWADA-PM): an easy-to-implement and rugged strategy. (March 2014) - Li, Fumin; Fast, Douglas M; Ploch, Stephen A
Background: Liquid microsampling can realize ethical benefits through reduced animal usage. It inherently deals with a minute amount of sample; for example, <30 µl of plasma, which is generally insufficient for multiple analyses.Results: We report accurate weighing and dilution-assisted plasma microsampling (AWADA-PM) that substantially increases sample sizes (e.g., by tenfold). Plasma samples are harvested from blood samples (∼70 µl) in capillaries. The plasma samples are weighed with a calibrated balance. The weights are converted to volumes using a standard plasma density of 1.025 g/cm 3 . Diluent is added with a calibrated pipette to the harvested plasma to achieve a tenfold dilution.Conclusion: The proof-of-concept for AWADA-PM was successfully demonstrated for the quantitation of acetaminophen in rat plasma (K2 EDTA) using liquid chromatography–tandem mass spectrometry employing water and blank rat plasma as diluents. The results clearly demonstrate that the AWADA-PM strategy is an easy-to-implement and reliable microsampling technology that has potential for full regulatory compliance.